1994
DOI: 10.1139/e94-047
|View full text |Cite
|
Sign up to set email alerts
|

A Holocene soil-geomorphic record from the Ham site near Frontier, southwestern Saskatchewan

Abstract: The soil-geomorphic evolution of a hillslope in hummocky moraine terrain in one of the most arid parts of the Palliser Triangle is reconstructed from ca. 12 600 BP to the present. A transect from a moraine plateau into an internally drained basin provided evidence for seven postglacial landscape cycles. Each cycle includes a phase of land-surface instability, marked by erosional and depositional imprints, and a phase of stability, marked by pedologic imprints. Five cycles of slopewash-dominated erosion left be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Other, more local, sources of dust have apparently produced thin loess mantles on stable upland surfaces in semiarid western North Dakota, but not thick deposits containing the Leonard Paleosol. Loess or clifftop eolian deposits that are of local origin, and not derived from large river floodplains, have been documented nearby in Saskatchewan (David, 1970;Vreeken, 1994) and South Dakota (Rawling and Fredlund, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Other, more local, sources of dust have apparently produced thin loess mantles on stable upland surfaces in semiarid western North Dakota, but not thick deposits containing the Leonard Paleosol. Loess or clifftop eolian deposits that are of local origin, and not derived from large river floodplains, have been documented nearby in Saskatchewan (David, 1970;Vreeken, 1994) and South Dakota (Rawling and Fredlund, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sources differ in the findings about the climate after the Hypsithermal. Klassen (1994), Sauchyn and Sauchyn (1991) and Vreeken (1986Vreeken ( , 1994 found evidence that the post-Hypsithermal climate was somewhat cooler and moister than the present climate; however, other authors, including Oetelaar (2004), concluded that after the Hypsithermal, the climate changed to conditions similar to those found in the historical record.…”
Section: Effect Of Holocene Paleoclimatesmentioning
confidence: 96%
“…ON SOIL FORMATION The land surface and the soils that formed on them were also affected by climate change in the Holocene. Numerous studies into climatic trends during the Holocene in the Northern Great Plains of North America have been done using pollen and chemical analysis from lake cores (e.g., Sauchyn and Sauchyn 1991;Klassen 1994;Yansa 1998;Last and Vance 2001) and stratigraphic soil records (Vreeken 1986(Vreeken , 1994Oetelaar 2004). Different methods result in variations of the dating of periods of landscape stability and instability, but broad lines of agreement exist.…”
Section: Effect Of Holocene Paleoclimatesmentioning
confidence: 99%
“…Multiple episodes of Holocene nonglaciogenic loess deposition have been documented in the central Great plains of the United States and in Saskatchewan, Canada under climatic and environmental conditions that are not dissimilar to the eastern Carpathian Basin (David, ; Clayton, Moran, & Bickley, ; Vreeken, ; Mason & Kuzila, ; Jacobs & Mason, ). These periods of nonglacigenic loess accumulation are related to increased aridity and/or large magnitude floods that decreased vegetative cover on floodplains promoting renewed aeolian transport of local Pleistocene loess deposits.…”
Section: Setting and Backgroundmentioning
confidence: 99%